The Peer Counseling Model in Adolescents Reproductive Health for Senior High School Students - Indah Nurfazriah; Deni Kurniadi Sunjaya; Susi Susanah (Universitas Islam Bandung, 2018)
Premarital sexual behavior in adolescents is at risk of sexual intercourse. One of the teenagers' factors in premarital sexual intercourse is a lack of knowledge about adolescent reproductive health. One method that can be given to increase knowledge about reproductive health is peer counseling. Peer counseling service improvement can be supported by the availability of modules or teaching materials to be used as a guide for peer counselors. The purpose of this study was to analyze the substance of the peer counseling module, analyze the perspective of the prospective module user on the development of peer counseling modules, and develop a model of the peer counseling module. The design of this study was the concurrent mixed method was divided into two stages, namely in-depth interviews with the experts and interviews and surveying with module users. The data was collected from the senior high school students in Cimahi and Bandung, West Java from March to July 2017. The result of this study showed that the substances developed in this module were the adolescents’ reproductive health, adolescents’ preparation in family planning, and adolescents’ ethics. Based on results of the analysis using the Rasch model, in the module user’s perspective, there is a need for the development of peer counseling modules. Evaluation of the module’s model from participants showed that they mostly agreed with the module’s model and the substances that were developed. MODEL MODUL KONSELING SEBAYA DALAM KESEHATAN REPRODUKSI REMAJA PADA SISWA SEKOLAH MENENGAH ATASPerilaku seksual pranikah pada remaja berisiko melakukan hubungan seksual. Salah satu faktor remaja melakukan hubungan seksual pranikah adalah pengetahuan tentang kesehatan reproduksi remaja yang kurang. Salah satu metode yang dapat diberikan untuk meningkatkan pengetahuan tentang kesehatan reproduksi adalah konseling sebaya. Peningkatan pelayanan konseling sebaya dapat ditunjang oleh ketersediaan modul atau bahan ajar sebagai panduan bagi konselor sebaya. Tujuan penelitian ini adalah menganalisis substansi modul konseling sebaya, menganalisis perspektif pengguna modul tentang pengembangan modul konseling sebaya, dan mengembangkan model modul konseling sebaya. Desain penelitian yang digunakan concurrent mixed methods yang dibagi menjadi dua tahap, yaitu wawancara mendalam dengan para pakar serta wawancara dan survei dengan pengguna modul. Data dikumpulkan dari siswa SMA di Cimahi dan Bandung, Jawa Barat mulai Maret hingga Juli 2017. Hasil penelitian menunjukkan bahwa substansi yang perlu dikembangkan dalam modul konseling sebaya adalah kesehatan reproduksi remaja, persiapan remaja dalam perencanaan keluarga, dan etika remaja. Berdasar atas hasil analisis menggunakan model Rasch, perspektif dari para pengguna modul adalah perlu pengembangan modul konseling sebaya. Evaluasi model modul dari partisipan menunjukkan bahwa kebanyakan mereka setuju dengan model modul dan substansi modul yang dikembangkan.